The value of immunomodulatory therapy (use of vaginal suppositories) in treatment of HPV-associated neoplasia - I N Kononova; T A Oboskalova; E S Voroshilina; Yu V Pertsova (IP Berlin A.V., 2014)
Comparative analysis of the results of the adjuvant therapy in 60 patients with HPV-associated cervical neoplasms. It is established that the use of local immunomodulatory therapy with Polyoxidonium before conducting destructive methods of treatment improves the state of local immunity, promotes the normalization of microflora of the vagina and elimination of human papillomavirus, increases the effectiveness of therapy, reduces the recurrence of the process.